Analisis Pengaruh Citra Perusahaan Dan Pemasaran Islam Terhadap Minat Beli Konsumen Perspektif Ekonomi Islam Pada Toko Gayatri - Muhammad Abdul Rozik Mubarok; Finny Ligery (Pusat Riset dan Inovasi Nasional, 2024)
This study discusses consumer purchase intention at a retail store, which is presumed to be influenced by corporate image and Islamic marketing. The purpose of this research is to analyze the effect of corporate image and Islamic marketing on consumer purchase intention at Toko Gayatri in Braja Harjosari Village. The background of this study is based on the importance of a positive corporate image and the application of Islamic values in enhancing consumer trust and purchase tendency. The research method used is a quantitative approach with a survey technique, where primary data were obtained through questionnaires distributed to 100 respondents who are consumers of Toko Gayatri. Data analysis was carried out using multiple linear regression with the assistance of SPSS. The results of the study show that corporate image has a positive and significant effect on consumer purchase intention. Islamic marketing is also proven to have a positive and significant effect on consumer purchase intention. Furthermore, corporate image and Islamic marketing simultaneously exert a strong influence on consumer purchase intention at Toko Gayatri. This research emphasizes that the better the corporate image presented and the more consistently Islamic marketing principles are applied, the higher the consumer purchase intention will be. Therefore, the management of Toko Gayatri needs to maintain a positive corporate reputation while integrating Islamic values into its marketing strategies.